ISPAD Clinical Practice Consensus Guidelines 2022: Type 2 diabetes in children and adolescents. Issue 7 (25th September 2022) - Shah, Amy S.; Zeitler, Philip S.; Wong, Jencia; Pena, Alexia S.; Wicklow, Brandy; Arslanian, Silva; Chang, Nancy; Fu, Junfen; Dabadghao, Preeti; Pinhas‐Hamiel, Orit; Urakami, Tatsuhiko; Craig, Maria E.
Abstract: Since the 2018 ISPAD guidelines on this topic, follow‐up of large cohorts from around the globe have continued informing the current incidence and prevalence of co‐morbidities and complications in young adults with youth‐onset type 2 diabetes (T2D). This chapter focuses on the risk factors, diagnosis and presentation of youth‐onset T2D, the initial and subsequent management of youth‐onset T2D, and management of co‐morbidities and complications. We include key updates from the observational phase of the multi‐center Treatment Options for Type 2 Diabetes in Adolescents and Youth (TODAY) clinical trial, the SEARCH for Diabetes in Youth (SEARCH) study and new data from the Restoring Insulin Secretion (RISE) study, a head‐to‐head comparison of youth onset vs adult‐onset T2D. We also include an expanded section on risk factors associated with T2D, algorithms and tables for treatment, management, and assessment of co‐morbidities and complications, and sections on recently approved pharmacologic therapies for the treatment of youth‐onset T2D, social determinants of health, and settings of care given COVID‐19 pandemic.